2016
DOI: 10.1038/srep35849
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Drug-Induced Sleep Computed Tomography in Adults With Obstructive Sleep Apnea

Abstract: Surgical success for obstructive sleep apnea (OSA) depends on identifying sites of obstruction in the upper airway. In this study, we investigated sites of obstruction by evaluating dynamic changes in the upper airway using drug-induced sleep computed tomography (DI-SCT) in patients with OSA. Thirty-five adult patients with OSA were prospectively enrolled. Sleep was induced with propofol under light sedation (bispectral index 70–75), and low-dose 320-detector row CT was performed for 10 seconds over a span of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 39 publications
0
35
0
Order By: Relevance
“…Previous studies performed during sleep using endoscopy, CT scan, and MRI have shown that the pharynx can obstruct at more than one site. 3,[22][23][24] Vroegop et al 22 performed drug-induced sleep endoscopy in 1,249 patients and showed that 68% had multilevel collapse. The most frequent combination was collapse of the palate and tongue base (26% of patients), followed by the palate and epiglottis (21% of patients).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies performed during sleep using endoscopy, CT scan, and MRI have shown that the pharynx can obstruct at more than one site. 3,[22][23][24] Vroegop et al 22 performed drug-induced sleep endoscopy in 1,249 patients and showed that 68% had multilevel collapse. The most frequent combination was collapse of the palate and tongue base (26% of patients), followed by the palate and epiglottis (21% of patients).…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous airflow has not been used in previous studies. 3,[22][23][24] Third, we used a small amount of CPAP in patients with cyclic obstructive apneas to increase endexpiratory pharyngeal dimensions and facilitate the distinction between the pharyngeal structures. CPAP was also used for similar reasons by Li et al 24 in a study using dynamic upper airway CT scan to determine the site of pharyngeal collapse during sleep.…”
Section: Discussionmentioning
confidence: 99%
“…Epiglottis collapse is commonly ignored at its role in contributing to OSA. In our previous study, epiglottis collapse existed in 25% of moderate to severe OSA patients [46] . Epiglottis collapse jeopardizes the use of CPAP and causes UPPP failure [16] , [17] .…”
Section: Intrapharyngeal Surgery By Mini-invasive Reconstructionmentioning
confidence: 79%
“…The cause can be attributable to inappropriate mode or incorrect position. In our previous study of drug-induced sleep computed tomography scan in recognizing the levels of obstruction, we found that tongue collapse can be identified as upper (body, 30%), lower (base, 37%), and upper followed by lower (biphasic, 33%) collapse models from dynamic change in sagittal view [46] . Upper and biphasic models comprise 63% in our study population with tongue collapse, which are likely to be misdiagnosed as A-P collapse of the soft palate in drug-induced sleep endoscopy [47] .…”
Section: Intrapharyngeal Surgery By Mini-invasive Reconstructionmentioning
confidence: 93%
“…This suboptimal outcome may be attributable to primary tongue collapse that compresses the soft palate and presents as A-P palatal obstruction. In our previous study of drug-induced sleep computed tomography scan, tongue obstruction can be identified as upper (body, 30%), lower (base, 37%), and upper followed by lower (biphasic, 33%) obstruction models 18 . Upper and biphasic tongue obstruction comprise 63% in whole tongue obstruction, which are likely to be misdiagnosed as A-P palatal obstruction in endoscopic examination.…”
Section: Discussionmentioning
confidence: 97%